FILSAFAT LINGKUNGAN PARADIGMA BARU UNTUK PARA ARSITEK - Siregar, Laksmi Gondokusumo (Bumi Lestari, 2010)
Eco-philosophy is philosophical vision of ecological harmony in very broad sense. It unifies both vision of humanity, nature or even universe as part of evolutionary procesw towards understanding of life, consciousness and philosophy of God As an architect, one is potentially altering his/her surroundings from natural environment to a more synthetic one.A deeply understanding of ecological philosophy leads to attitudes and action that bring sustainable principle as primary basis for every architect to aware about the possibly harmful impact of their jobs to environment. It is a sense of responsibility that is to make the earth a harmonious place worth for living.